Design Of an Appsheet-Based Inventory Management System Using the RAD Method - Muhammad Naufal Hafidh Shidqi; Agus Setiawan; Wiku Larutama (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Competition in the manufacturing industry requires companies to improve operational effectiveness, particularly in inventory management. PT XYZ, which initially operated in the metal fabrication services sector, has expanded into manufacturing; however, during this transition, inventory was still recorded manually, leading to data discrepancies and operational issues. Observations from a stocktaking process conducted in June 2025 indicated that inventory accuracy was only 76%, resulting in delivery delays, inventory accumulation, and potential financial losses. This study aims to design and implement an AppSheet-based inventory management system to address these problems. The system was developed using the SDLC method with RAD approach, emphasizing rapid development and user involvement. The developed system includes features for recording incoming goods, outgoing goods, production output, and real-time stock monitoring. System functionality was verified through black-box testing, while system acceptance was evaluated using User Acceptance Testing and a user satisfaction survey. The results indicate that all system functions operated as expected and met user requirements, achieving an average user satisfaction score of 4,25. Although the evaluation of long-term improvements in inventory accuracy remains limited, the system is considered reliable and suitable for daily operational use. It is expected to improve the consistency of inventory data. Keywords: Inventory Management System, AppSheet, RAD